Krogius, Georg → Alopaeus, Carl Elias‎ (1850) - Krogius, Georg.; Krogius; Alopaeus, Carolus Elias, 1793-1851; Nationalbiblioteket (YBc Muut kirjeet)
Yksi kirje Georg Krogiukselta Carl Elias Alopaeukselle.
Keywords: kirjeet